Brain areas modulation in consciousness during sevoflurane anesthesia - Lyu, Jie; Cai, Huajing; Chen, Yeru; Chen, Gang (Frontiers in Integrative Neuroscience, 2022)
Sevoflurane is presently one of the most used inhaled anesthetics worldwide. However, the mechanisms through which sevoflurane acts and the areas of the brain associated with changes in consciousness during anesthesia remain important and complex research questions. Sevoflurane is generally regarded as a volatile anesthetic that blindly targets neuronal (and sometimes astrocyte) GABAA receptors. This review focuses on the brain areas of sevoflurane action and their relation to changes in consciousness during anesthesia. We cover 20 years of history, from the bench to the bedside, and includes perspectives on functional magnetic resonance, electroencephalogram, and pharmacological experiments. We review the interactions and neurotransmitters involved in brain circuits during sevoflurane anesthesia, improving the effectiveness and accuracy of sevoflurane future application and shedding light on the mechanisms behind human consciousness.